Automatic threshold decision using maximum mismatched correlation value for direct sequence code aquisition - Natarajan Pasupathy Prasad (2008)
This project work is done on automatic threshold decision using a maximum mismatched correlation (MMC) value in a direct sequence spread spectrum (DS-SS) serial acquisition system. For received spread spectrum with varying signal-to-noise ratios (SNRs), this MMC scheme is able to detect a desired threshold value in the search mode, i.e. a maximum mismatched correlation value, which is utilized as a threshold for the verification mode. Thus, there is no need to determine a threshold by applying the conventional Neyman-Pearson criterion. The proposed acquisition scheme is compared to the acquisition scheme based upon the Neyman-Pearson criterion, and a significant improvement of performance is shown. Analysis of system performance in both the search and verification modes are presented, and key quantities such as the false alarm probability (F AP) and detection probability (DP) are derived.